Development of Probiotic Products Made From Soy Milk With The Addition of Red Dragon Fruit Extract Concentration As a Source of Antioxidants - Wati, Fatma; Jamaluddin, Jamaluddin; Sukainah, Andi (Journal of Agroscience Indonesia, 2024)
This research is an experimental study that aims to determine the effect of the concentration of red dragon fruit extract on the quality and antioxidant activity of probiotic soyghurt products or fermented soy milk. This study used an experimental method with a RAL experimental design consisting of 4 treatments and 3 replications. The treatment variable in this study was the addition of red dragon fruit extract with concentrations of K(0%), A(5%), B(10%), and C(`15%), while the observation variable in this study was the total calculation of LAB, protein content, fat content, vitamin C content, pH, total acid, antioxidant activity analysis, and organoleptic testing (color, aroma, texture, and taste). The data obtained from the results of this study were tested for normality and homogeneity using SPSS version 20 software. Then, the analysis was carried out using analysis of variance (ANOVA) and continued with Duncan's further test. Based on the results of normality and homogeneity tests, all data were normally distributed and homogeneous. Based on the analysis of variance ANOVA obtained Fcount>Ftable 5% level. This shows that all treatments have a significant effect on the observed variables in the study. The results showed that treatment C was the best treatment because it was preferred by the panelists with a total BAL value of 11.23 Log Cfu/ml, 6.1% protein content, 5.32% fat content, 0.09% vitamin C, pH 4.65. , total acid 1.74%, and antioxidant activity 62.95%.